DEVELOPMENT OF AUGMENTED REALITY BOOKS AS A LEARNING MEDIUM FOR THE STRUCTURE AND FUNCTION OF FLOWERING PLANT PARTS USING THE MARKER-BASED TRACKING METHOD - Tanta Fahira; Sarini Vita Dewi (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2026)
Science learning plays an important role in developing students’ understanding of natural phenomena through conceptual mastery and application in everyday life. One science topic that requires strong conceptual and visual understanding is the structure and function of plant parts, particularly complete flowers. However, science learning on this topic still largely relies on textbooks and two-dimensional images as instructional media. These media are not able to clearly present the shape, position, and function of flower parts, causing students to have difficulty visualizing abstract concepts. As a result, students’ understanding of the material is not yet optimal. Therefore, this study aims to develop and implement an Augmented Reality Book (AR Book) using a marker-based tracking method as a learning medium, as well as to determine its feasibility and effectiveness in the learning process. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were fourth-grade students of MIN 8 Aceh Besar. Data were collected through validation by media experts and subject-matter experts, student response questionnaires, and analysis of learning media implementation results. The results showed that the developed AR Book obtained a feasibility score of 90% from media experts and 91% from subject-matter experts, both of which fall into the “very good” category. In addition, the results of its implementation with students showed a percentage of 94%, also categorized as very good. Based on these findings, it can be concluded that the marker-based tracking AR Book is feasible and effective as a science learning medium and is able to improve students’ understanding, interest, and engagement in learning the structure and function of complete flower plant parts